Heavy Metals and Antibiotics Resistance Pattern of Bacteria Isolated from Brewery and Plastic Industries Effluent Wastes - E. L. , Okoye; B. O. , Uba; C. , Ekwueme; T. C. , Azubike; J. C., Ugoma, (African Journal of Education,Science and Technology (AJEST), 2017)
In this study, waste water samples from brewery and plastic industrial area were collected and used to determine the antibiotics and heavy metal resistance patterns for bacteria. The preliminary analyses of the samples were taken using atomic absorption spectrophotometer (Varian AA240). Two heavy metal resistant bacteria were isolated and identified as Bacillus sp. and Pseudomonas sp. from oxidation ditch of waste water plants using GSP agar and nutrient agar. The minimum inhibitory concentration of isolates against the heavy metals was determined using spectrophotometric analysis (Astell UV-Vis grating 752W). The identified isolates were resistant to copper, lead, chromium but sensitive to zinc and iron on their culture plates. Forty percent (40%) of Bacillus sp. were resistant to heavy metals while fifty percent (50%) of Pseudomonas sp. were resistant to heavy metal. Iron was found to have the highest percentage of sensitivity while chromium has the lowest percentage. Bacillus sp. was sensitive to all antibiotics used while Pseudomonas sp. was only sensitive to gentamycin, rifampicin and ampiclox. Thus, these heavy metal resistant bacteria could be useful for the bioremediation of heavy metal contaminated ecosystem and antibiotics that are inhibitory can be used for bacterial treatment of Bacillus and Pseudomonas species infections.